Odpowiedź :
a) 2a(3b - 4a) - 3b(a - 2b) = 6ab - 8a² - 3ab + 6b² = 3ab - 8a² + 6b²
b) 2(x - y) - 8(x - y) + 4(x - y) = 2x - 2x - 8x + 8y + 4x - 4y = -2x + 2y
c) (3x - 2)(3x+ 2) = (3x)² - 2² = 9x² - 4
d) (3x - 12)/3 - (2x - 4)/2 = 3(x - 4)/3 - 2(x-2)/2 = x - 4 - (x - 2) = x - 4 - x + 2 = -2
liczę na naj :)
Odpowiedź:
a) 2a( 3b − 4a ) −3b (a -2b ) = 6ab - 8a² - 3ab + 6ab = 9ab - 8a²
b) 2(x - y) -8(x- y) +4(x- y) = 2x - 2y - 8x + 8y + 4x - 4y = -2x + 2y
c) (3x- 2)(3x+ 2)= 9x + 6x - 6x - 4 = 9x - 4
d) (3x - 12) ÷ 3 - (2x - 4) ÷ 2= x - 4 - x - 2 = -6
Mam nadzieje, że pomogłam :)
Szczegółowe wyjaśnienie: